Effects of Probiotics and Vitamin B Supplementation on IFN-γ and IL-12 Levels During Intensive Phase Treatment of Tuberculosis - Budi Suprapti; Suharjono Suharjono; Rahmawati Raising; Yulistiani Yulistiani; Zamrotul Izzah; Wenny Putri Nilamsari; Prastuti Asta Wulaningrum; Arief Bachtiar (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
Tuberculosis is an acute infectious disease that primarily affects the lungs. Probiotics supplementation can increase the number and activity of NK cell in peripheral blood by modulation of IL-12, thus increasing IFN-γ production by Th1 response. Vitamin B1 acts on macrophages and affects neutrophil motility. Vitamin B6 is associated with the release of cytokines and the responsiveness of NK cells, while vitamin B12 affects to lymphocytes, Tcell proliferation, CD4+ ratios, and NK cell activity. To analyze the effects of probiotics and vitamin B1, B6, B12 supplementation on IFN-γ and IL-12 levels during intensive phase of antituberculosis treatment. The study was pre-post test randomised control by time series. The control group was TB patients with standard therapy of antituberculosis and vitamin B6, while the intervention group was TB patients receiving therapy plus once daily probiotics and vitamin B1, B6, B12supplementation during the intensive phase. Blood samples were withdrawn at baseline, one month, and two months after therapy to measure plasma IFN-γ and IL-12 levels using the ELISA method. Twenty two patients were divided equally into two groups. There was a tendency to greater increase of IFN-γ in the first month of the intervention group, followed by a significant decline after two-month therapy (p < 0.05). In both groups there was a rise in IL-12 levels after one month followed by a decrease in the second month (p > 0.05). However, the percentage was higher in the supplementation group. Adding probiotics and vitamins B1, B6, B12 could improve immune response through IL-12 and IFN-γ modulation during intensive phase therapy.